Authority of Security Council to Stop the Jurisdiction of International Criminal Court: Case Study of Security Council Resolution Number 1497 (2003) - Sefriani Sefriani (Fakultas Hukum Universitas Islam Indonesia, 2009)
Though United Nation Security Council is a permanent organ within the UN, this organ is not party of the Rome Statute 1998. As Such, the Security Council is not entitled by the right to amend section 16 of the Rome Statute 1998 which eliminate the jurisdiction of ICC on the UN troops who are the citizen of Non Party in the Rome Statute 1990Keywords: International Criminal Court, Security Council's Resolution no. 1497 of 2003